Strenuous Physical Training, Physical Fitness, Body Composition and Bacteroides to Prevotella Ratio in the Gut of Elderly Athletes - Šoltys, Katarína; Lendvorský, Leonard; Hric, Ivan; Baranovičová, Eva; Penesová, Adela; Mikula, Ivan; Bohmer, Miroslav; Budiš, Jaroslav; Vávrová, Silvia; Grones, Jozef; Grendar, Marian; Kolísek, Martin; et al. (Frontiers in Physiology, 2021)
Regular physical activity seems to have positive effect on microbiota composition of elderly, but little is known whether strenuous endurance training might bring any further benefits. To gain an insight into the physiology of elderly and identify biomarkers associated with endurance training we combined different omics approaches. We aimed to investigate the gut microbiome, plasma composition, body composition, cardiorespiratory fitness, muscle strength of lifetime elderly endurance athletes (LEA) and healthy controls (CTRL) meeting global recommendations on physical activity. We involved 22 male participants in this cross-sectional study meeting strictly set inclusion and exclusion criteria. Microbiome analysis was performed using collected stool samples further subjected to 16S rRNA gene analysis. NMR-spectroscopic analysis was applied to determine and compare selected blood plasma metabolites mostly linked to energy metabolism. The random forest machine learning analysis identified VO2max, BMI, and Bacteroides to Prevotella ratio as suitable, joined predictors with excellent ability to discriminate between subjects from LA and CTRL groups. Even though lifelong endurance exercise does not bring any significant benefit regarding overall gut microbiota diversity, strenuous athletic training is associated with higher cardiorespiratory fitness, lower body fat and some favorable gut microbiota composition, all factors associated with slower rate of biological aging.